Effect of non‐solvent on the synthesis of polyvinylidene fluoride membranes for vacuum membrane distillation desalination. Issue 1 (21st December 2021) - Sachett, Felipe Henrique; Duarte, Jocelei; Zeni, Mara; Costamilan, Leonardo; Poletto, Matheus; Baldasso, Camila
Abstract: The need for freshwater boosted the research for alternative technologies with a cleaner and more efficient approach. Membrane distillation (MD) stands out due to its efficiency in purifying aqueous solutions and easy operation. Thus, this work aims at developing and characterizing polyvinylidene fluoride membranes using the non‐solvent phase inversion (NIPS) methodology for the MD process. Distilled water and ethanol (at different proportions) were tested as non‐solvent and N'N'‐dimethylformamide as solvent. The morphology, crystallinity, and porosity of each sample were determined. The utilization of ethanol as non‐solvent produced more hydrophobic membranes with higher liquid entry pressure. Scanning electron microscope analysis showed that different proportions of water and ethanol changes the morphology of the resulting membrane, with clear influence on the formation of macrovoids. The samples crystallinity was over 54% and the porosity, over 55%. The sample with best results in the vacuum MD process prpesented an average of over 98% of salt retention during a period of 6 h. This work shows the beneficial influence ethanol as non‐solvents for the preparation of PVDF membranes for the process of hydrophobic vacuum MD.